2019
DOI: 10.3390/nu11071657
|View full text |Cite
|
Sign up to set email alerts
|

Differential Stimulation of Post-Exercise Myofibrillar Protein Synthesis in Humans Following Isonitrogenous, Isocaloric Pre-Exercise Feeding

Abstract: The aim of this study was to test the effects of two disparate isonitrogenous, isocaloric pre-exercise feeds on deuterium-oxide (D2O) derived measures of myofibrillar protein synthesis (myoPS) in humans. Methods: In a double-blind parallel group design, 22 resistance-trained men aged 18 to 35 years ingested a meal (6 kcal·kg−1, 0.8 g·kg−1 carbohydrate, 0.2 g·kg−1 fat) with 0.33 g·kg−1 nonessential amino acids blend (NEAA) or whey protein (WHEY), prior to resistance exercise (70% 1RM back-squats, 10 reps per se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…In a recent study, using the D 2 O-method, we reported that acute ingestion of 0.33 g•kg −1 of whey protein increased postexercise myoFSR,~30 % for~5 h, in a young healthy resistance-trained cohort [7]. In the present study, the D 2 O-tracer technique was employed to measure myoFSR, but this time measuring the effect of 0.33 g•kg −1 •d −1 of supplemental whey protein over multiple days of RT.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a recent study, using the D 2 O-method, we reported that acute ingestion of 0.33 g•kg −1 of whey protein increased postexercise myoFSR,~30 % for~5 h, in a young healthy resistance-trained cohort [7]. In the present study, the D 2 O-tracer technique was employed to measure myoFSR, but this time measuring the effect of 0.33 g•kg −1 •d −1 of supplemental whey protein over multiple days of RT.…”
Section: Discussionmentioning
confidence: 92%
“…In order to maximise postexercise/postprandial myoPS and ensure compliance to the study diet, morning ingestion of 0.33 g•kg −1 •d −1 of protein, from a whey protein concentrate supplement [20], after an overnight fast (~10 h postabsorptive, ~0.5 pre-exercise [21]), was conducted. The control group consumed an isonitrogenous formulation of nonessential amino acids that does not stimulate myoPS (Carbery Food Ingredients, Ireland) (Appendix C) [7]. Supplements were mixed with 500 ml water, identically flavoured (vanilla) and administered in a double-blind fashion.…”
Section: Pre-study Dietary Assessment Control and Supplementationmentioning
confidence: 99%
“…Non-essential amino acids (NEAA) are not required for the acute anabolic response to EAA consumption [2][3][4]. This is because NEAA are normally produced in the body at fast enough rates to avoid deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…EAA cannot be produced in the body, but are primarily responsible for the stimulation of muscle protein synthesis [1]. Non-essential amino acid consumption, with or without concomitant EAA consumption, fails to affect protein synthesis in healthy, well-nourished volunteers, whether at rest [1,2] or after exercise [3,4]. The response of muscle protein synthesis following ingestion of a composition of free EAA is more than twice the response to consumption of a comparable dosage (g/g) of whey protein isolate [5].…”
Section: Introductionmentioning
confidence: 99%
“…While elevated levels of EAA strongly increase anabolic signalling and MPS [8,25], NEAA do not have a stimulatory effect on MPS in vitro [17] or in vivo [6,26,27]. It has been demonstrated that significant stimulation of MPS requires at least a two-fold increase of plasma aminoacidemia above basal levels [28].…”
Section: Discussionmentioning
confidence: 99%